Therapy of childhood acute lymphoblastic leukemia in resource-poor geospaces - Moisés M. Gallardo-Pérez; Moisés M. Gallardo-Pérez; Robert Peter Gale; Oscar A. Reyes-Cisneros; Oscar A. Reyes-Cisneros; Daniela Sánchez-Bonilla; Daniela Sánchez-Bonilla; José A. Fernández-Gutiérrez; José A. Fernández-Gutiérrez; Wendy Stock; Iván Murrieta-Álvarez; Iván Murrieta-Álvarez; et al. (Frontiers in Oncology, 2023)
The therapy of children with acute lymphoblastic leukemia (ALL) in limited resource geospaces is challenging and must balance safety, efficacy, availability, and affordability. We modified the control arm of the St. Jude Total XI protocol for outpatient delivery including once-weekly daunorubicin and vincristine in initial therapy, postponing intrathecal chemotherapy until day 22, prophylactic oral antibiotics/antimycotics, use of generic drugs, and no central nervous system (CNS) radiation. Data were interrogated from 104 consecutive children ≤12 years (median, 6 years [interquartile range (IQR), 3, 9 years]. All therapies were given in an outpatient setting in 72 children. Median follow-up is 56 months (IQR 20, 126 months). A total of 88 children achieved a hematological complete remission. Median event-free survival (EFS) is 87 months [95% confidence interval (CI), 39, 60], 7.6 years in low-risk children (3.4, 8 years) whereas 2.5 years (1, 10 years) in high-risk children. The 5-year cumulative incidence of relapse (CIR) is 28% (18, 35%), 26% (14, 37%) in low-risk children and 35% (14, 52%) in high-risk children. Median survival for all subjects is not reached but must exceed 5 years. A total of 36 children relapsed at a median of 12 months (5, 23 months). Outcomes were comparable to those reported in the control arm of the Total Therapy XI study, but inferior to current treatment protocols in high-income countries. The average cost of the first 2 years of therapy was $28,500 USD compared with an average cost of approximately $150,000 USD in the US, an 80% saving. In conclusion, using an outpatient-based modification of the St. Jude Total XI protocol, we obtained good results with relatively few hospitalizations or adverse events and at a substantial saving. This model can be applied in other resource-poor geospaces.